2007
DOI: 10.1002/pssa.200674351
|View full text |Cite
|
Sign up to set email alerts
|

Porous silicon‐based polymer replicas formed by bead patterning

Abstract: Monodisperse, micrometer‐sized polymer beads can be imparted with a porous nanostructure by softening them into a porous silicon photonic crystal template. Infiltration of the polymer and replication of the photonic spectral properties is verified by optical reflectivity measurements of the beads as they infuse into the nanostructure. The polymer beads can be removed from the porous Si template by dissolution of the template with a basic solution. This treatment destroys the photonic properties, although scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…For example, ring opening metathesis polymerisation of norbornene has been used to create flexible 1-D photonic crystals of pSi [36]. pSi has also been employed as a template for polymer replicas, with various polymers including poly(styrene), PLLA and poly(methyl)methacrylate [37][38][39]. Electropolymerisation has given pSi-polyaniline composite media properties suitable for silicon-based light emitting diodes [40].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ring opening metathesis polymerisation of norbornene has been used to create flexible 1-D photonic crystals of pSi [36]. pSi has also been employed as a template for polymer replicas, with various polymers including poly(styrene), PLLA and poly(methyl)methacrylate [37][38][39]. Electropolymerisation has given pSi-polyaniline composite media properties suitable for silicon-based light emitting diodes [40].…”
Section: Introductionmentioning
confidence: 99%
“…Because they can concentrate molecules within their nanostructure and protect them from the body's natural immunological responses, the particles can potentially carry a much higher dose than could be allowed with a free drug injection. The particles can also be manufactured with well-defined shapes and dimensions, allowing the reproducible loading and release of precise quantities [44][45][46].…”
Section: Particle Formulationsmentioning
confidence: 99%
“…The film can then be converted into microparticles by ultrasonic fracture. Conventional lithography [44,45] or microdroplet patterning [46,47] methods can also be used if particles with more uniform shapes are desired.…”
Section: Electrochemical Etchingmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] The porous structure is controlled by the density of the etching current, the resistivity of silicon, and the concentration of the etching solution. pSi particles with defined size and shape have been fabricated using conventional photolithography,[9-11] nanoparticle lithography [12] or microdroplet patterning. [13] Recently Ryckman et al [14] reported a rapid and low-cost approach for patterning pSi by direct imprinting of micro- and nanoscale features.…”
Section: Novel Techniques For Psi Particle Fabricationmentioning
confidence: 99%